The other twizzles - Ogilvie, R. S. (The Professional Skater PS Magazine, 2013)
Twizzles are a series of traveling unchecked three-turns on one foot that are rotated with a continious and uninterrupted action. The four different types of entry edges for twizzles are forward inside, forward outside, backward inside and backward outside. A great twizzle travels one blade length or less between the cusps of the turns. It will be closer to two blade length at lower levels.